Seismic Structure of the Antarctic Upper Mantle Imaged with Adjoint Tomography. Issue 3 (13th March 2020) - Lloyd, A. J.; Wiens, D. A.; Zhu, H.; Tromp, J.; Nyblade, A. A.; Aster, R. C.; Hansen, S. E.; Dalziel, I. W. D.; Wilson, T.J.; Ivins, E. R.; O'Donnell, J. P.
Abstract: The upper mantle and transition zone beneath Antarctica and the surrounding oceans are among the poorest‐imaged regions of the Earth's interior. Over the last 15 years, several large broadband regional seismic arrays have been deployed, as have new permanent seismic stations. Using data from 297 Antarctic and 26 additional seismic stations south of ~40°S, we image the seismic structure of the upper mantle and transition zone using adjoint tomography. Over the course of 20 iterations, we utilize phase observations from three‐component seismograms containing P, S, Rayleigh, and Love waves, including reflections and overtones, generated by 270 earthquakes that occurred from 2001–2003 and 2007–2016. The new continental‐scale seismic model (ANT‐20) possesses regional‐scale resolution south of 60°S. In East Antarctica, thinner continental lithosphere is found beneath areas of Dronning Maud Land and Enderby‐Kemp Land. A continuous slow wave speed anomaly extends from the Balleny Islands through the western Ross Embayment and delineates areas of Cenozoic extension and volcanism that span both oceanic and continental regions. Slow wave speed anomalies are also imaged beneath Marie Byrd Land and along the Amundsen Sea Coast, extending to the Antarctic Peninsula. These anomalies are confined to the upper 200–250 km of the mantle, except in the vicinity of Marie Byrd Land where they extend into the transition zone and possibly deeper. Finally, slow wave speeds along the Amundsen Sea Coast link to deeper anomalies offshore, suggesting a possible connection with deeper mantle processes. Key Points: The strongest variability in East Antarctic lithosphere is observed across Dronning Maud Land and Enderby‐Kemp Land A slow anomaly extends from the Balleny Islands through the western Ross Embayment, delineating areas of Cenozoic extension and volcanism Slow anomalies imaged beneath Marie Byrd Land, the Amundsen Sea Coast, and the Antarctic Peninsula reflect hotspot and subduction processes